2004
DOI: 10.1016/s0022-5223(04)00870-0
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional echocardiography–guided beating-heart surgery without cardiopulmonary bypass: A feasibility study

Abstract: Real-time 3-dimensional echocardiography provides adequate imaging and anatomic detail to act as a sole guide for surgical task performance. These initial experiments demonstrate the feasibility of beating-heart direct or patch closure of atrial septal defects and mitral valve plasty without cardiopulmonary bypass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…As standard 3D ultrasound image is a plan view and lacks a sense of space, so conventional 3D image can only show two-dimensional (vertical and transverse) relations of tissue structures, while it present the adjacent and far-away hierarchical structures mainly by means of shadow and brightness [10][11][12][13] . S-3DE can vividly and clearly present the nearby and distant, and spatial relationships of tissue structures and thereby greatly enhance the resolution of 3D images.…”
Section: Discussionmentioning
confidence: 99%
“…As standard 3D ultrasound image is a plan view and lacks a sense of space, so conventional 3D image can only show two-dimensional (vertical and transverse) relations of tissue structures, while it present the adjacent and far-away hierarchical structures mainly by means of shadow and brightness [10][11][12][13] . S-3DE can vividly and clearly present the nearby and distant, and spatial relationships of tissue structures and thereby greatly enhance the resolution of 3D images.…”
Section: Discussionmentioning
confidence: 99%
“…The development of new surgical procedures in the future should enable operations like ASD occlusion or mitral valve repair on the beating heart under 3D echocardiographic control. Suematsu et al (15)(16)(17)(18) have demonstrated the feasibility of such procedures in their latest studies, whereby they performed the studies on the model with transthoracic RT3DE systems. As the authors noted, RT3D-TEE would be necessary for clinical applications.…”
Section: Perspectives and Clinical Implications Of Rt3d-teementioning
confidence: 99%
“…Several approaches to intracardiac therapy have been attempted via direct access through the left [1] or right atrial appendage [2,3] for mitral valve replacement or atrial septal defect (ASD) repair, apical access through the left ventricle (LV) for aortic valve implantations [4], or intravascular access (catheter-based) for radio-frequency ablation therapy or valve repair [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%